Causes, nature and toxicology of fentanyl-analogues associated fatalities: a systematic review of case reports and case series - Rauf, Umaani; Ali, Majid; Dehele, Inderpal; Paudyal, Vibhu; Elnaem, Mohamed Hassan Abdelaziz; Cheema, Ejaz (Dove Medical Press, 2021)
Objective: Mortalities due to fentanyl derivatives are on the rise with novel fentanyl analogues and still emerging on the global illicit drug market. They are highly potent and very fatal in low doses, yet there has been a lack of systematic research surrounding this subject. This review aims to assess the causes, nature, and toxicology of fatalities associated with fentanyl analogues. Methods: Five databases: Scopus, Embase, Medline, PubMed and Google Scholar were searched from inception to October 2020 to identify case studies and case series reporting fentanyl analogue-related fatalities. Two independent reviewers screened and selected the articles followed by the data extraction from each article, which included demography, route of administration, causes and nature of death, and the fentanyl analogue implicated. All articles were then subject to quality assessment tools developed by the Joanna Briggs Institute (JBI). A narrative synthesis was undertaken. Results: The initial data search yielded 834 articles, only 14 of which met the inclusion criteria – this included nine case reports and five case series. Of the 1079 fentanyl-analogue related deaths reported, the majority of them occurred in the US (n=1044, 96.8%). The majority of fatalities were male (n=766, 71%), white (n=884, 87%) and in the age ranges 25– 34 and 35– 44 years (30.5% and 29.6%, respectively). The most common route of administration was intravenous (n=319, 66%) and the manner of death was almost exclusively accidental (99.7%). The predominant cause of death was fentanyl-analogue toxicity (n=292, 85.4%) and involved mixed drug toxicity (n=47, 13.7%). The mean post-mortem fentanyl analogue concentration was 31.6 ng/mL. Conclusion: Most fatalities were reported in the US involving young white males. Overdose through intravenous administration and by mixed drug toxicities with other opioids were the major causes of death. Deaths reported in peer-reviewed literature were relatively less than those reported by real-world data.